Impact of Emotional Support on Wellbeing, Mediating Role of Social Undermining: A Study of Academia in Balochistan. - Shaheen, Rubina; Bano, Safia; Ahmed, Jameel (American Journal of Psychology, 2021)
Purpose: The concept of negative behaviors in organizational psychology is at its emerging stage. Negative behaviors not only affect the well-being of the employees but also the overall performance of the organization. The purpose of this study was to investigate the association between emotional support (from co-workers) and employees' wellbeing in the presence of social undermining as a mediator. Materials and Methods: This study was quantitative. Cross-sectional and convenience sampling design (non-probability sampling technique) was applied to collect the data through questionnaires from the participants by using the survey method. Data was gathered from 287 Lecturers, Assistant Professors, and Professors from different public and private universities of Balochistan. Process Macro was applied to find the direct and indirect effect of emotional support on employees "˜wellbeing. Findings: Results showed that emotional support positively influenced wellbeing while social undermining partially mediates the relationship between emotional support and wellbeing. Recommendation: These findings can be applied in organizations to improve the wellbeing of the employees and minimize the negative behaviors in an organizational setting.